Quantitative and qualitative assessment of the wear pattern of two attachment systems of dissimilar materials for mandibular implant-retained overdentures: an in-vitro study - Rania E. Ramadan; Faten S. Mohamed; Mervat E. Abd-Ellah (BMC, 2023)
Abstract Background Attachment material is one of the contributing factors to the degree of wear of the attachment components in mandibular implant-retained overdentures. The purpose of this in vitro study was to compare the wear behavior of 2 different attachment systems of dissimilar materials in mandibular implant-retained overdentures by qualitative and quantitative methods. Methods Two attachment systems of different materials were utilized (n = 16); Titach (Dental Evolutions Inc, Beverly Hills, CA, USA) with a titanium-to-titanium interface and Locator R-Tx (Zest Anchors Inc, Escondido, CA, USA) with a titanium-to-nylon interface. One thousand cycles of overdenture insertion and removal simulating 1-year clinical use were performed. All matrices were removed from the overdentures and all patrices were unscrewed from the implants for wear assessment quantitively using a stereomicroscope and qualitatively using a scanning electron microscope. Data were analyzed by using an independent sample t test. Results After cyclic loading, stereomicroscopic findings showed that the Titach group had statistically significant higher wear value than the Locator R-Tx group (p < 0.001). Moreover, scanning electron microscopy images showed noticeable abrasion in Titach patrix at the area of highest convexity. However, the Locator R-Tx matrix displayed an apparent tear of rubber inserts. Conclusions Titach attachment with the titanium-to-titanium interface revealed more wear than Locator R-Tx attachment with the titanium-to-nylon interface. Thus, the type of attachment material influences the degree of wear of the attachment components.